CRIMINAL LIABILITY FOR PERPETRATORS OF VANDALISM OBSTRUCTION OF JUSTICE EVIDENCE IN THE PROCESS INVESTIGATION OF CORRUPTION (STUDY OF DECISION NUMBER 6/PID.SUS-TPK/2024/PN. PGP) - Rahmad Romy Agustiando Tampubolon; Danial Syah; Panca Sarjana Putra (LPPM YPITI, 2026)
Obstruction of justice, which is the act of deliberately obstructing or thwarting the investigation process, can interfere with the law enforcement process and create distrust in the justice system. The results of the research and discussion show that the form of the perpetrator obstructing the investigation (obstruction of justice) in the criminal act of corruption is the provisions of Article 21 of Law No. 31 of 1999 concerning the Eradication of Corruption Crimes. Criminal liability for perpetrators of obstruction of justice in corruption cases can be charged through Article 221 of the Criminal Code and Article 21 of Law No. 31 of 1999. The perpetrator of obstruction of justice in the corruption case of Toni Tamsil based on Decision Number 6/Pid.Sus-TPk/2024/PN Pgp has been legally and convincingly proven guilty of committing a criminal act by deliberately obstructing the investigation of a corruption case. As a result of his actions, the perpetrator was sentenced to imprisonment for 3 (three) years.